Menuju Desa Cerdas: Meningkatkan Literasi Digital Masyarakat Desa - Achmad Fikri Sallaby; Liza Yulianti; Maryaningsih Maryaningsih; Edy Hermansyah; Saika Damaiyanti (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This community service activity is motivated by the low level of digital literacy among rural communities, which affects the optimal use of technology in daily life. The main problems include limited understanding of internet usage, lack of awareness in using social media wisely, and risks of digital technology misuse. The purpose of this activity is to improve community knowledge and skills in utilizing digital technology productively. The methods used include socialization, training, and mentoring with a participatory approach. The activity was conducted in Sri Kuncoro Village, Central Bengkulu Regency, involving the community, village officials, and digital communities. The results show an increase in participants’ understanding of accessing information, using social media wisely, and basic digital security awareness. Therefore, this activity contributes to supporting the development of adaptive rural communities in the digital era.